Association between playing tactics and creating scoring opportunities in counterattacks from United States Major League Soccer games - Gonzalez-Rodenas, J.; Lopez-Bondia, I.; Calabuig, F.; Perez-Turpin, J. A.; Aranda, R. (International Journal of Performance Analysis in Sport, 2016)
The aim of this study was to examine the effects of playing tactics on creating scoring opportunities in counterattacks from the United States Major League Soccer (MLS) 2014 season. The sample included 452 counterattack possessions, corresponding to 30 randomly selected matches. Multidimensional data from 14 categorical variables were analysed by means of a descriptive analysis and binary logistic regression. Counterattacks that started in the pre-offensive zone and had initial penetration were more effective in creating scoring opportunities than those that started in the defensive zone